Incidence of pollinating agents on the fertilization of the cocoa flower (Theobroma cocoa L.) - García García, Vianka Stéfany (2022)
Cocoa (Theobroma cacao L.) is a crop of economic importance distributed in 50 countries. It has great connotation in the international market and the chocolate industry. Its productivity in the field is limited by biotic and abiotic conditions; the same ones that affect the fertilization of the flower. For this reason, the objective of this documentary research work is to know the incidence of more efficient pollinating agents on the fertilization of the cocoa flower. The bibliographic review was based on collecting information from primary sources that expose results of studies on entomophilous pollination of cocoa crop flowers, giving greater importance to research carried out in Ecuador. Emphasis was placed on the biotic factors of the agro-system of cocoa cultivation, such as the tree species that favor the habitat of the different pollinating agents; among the abiotic factors are wind, water, temperature, humidity and soil. In the consulted literature, it was found that the most relevant benefits of the presence of pollinators in the cocoa crop are the increase in fertilized flowers and therefore the production of cobs. It is concluded that the interaction of the different populations of pollinating agents with biotic and abiotic factors within the crop ecosystem favors cocoa production. Therefore it is advisable to use good techniques in the management of the plantation to guarantee the presence of pollinators.